Pelatihan Pembuatan Media Pembelajaran Interaktif untuk Meningkatkan Kemampuan Berpikir Kritis Pada Guru SMP Negeri Buti - Mutiya Oktariani; Damayanti; Acep Fatchuroji; Prima Lestari Situmorang (Jurnal Transformasi Pendidikan Indonesia, 2023)
SMP Negeri Buti is one of the state schools that implements the latest curriculum but is hampered by students' unsupported critical thinking abilities. To improve critical thinking skills, teachers need to receive training in creating interactive learning media that supports improving critical thinking skills such as websites.quizzwhizzer. Quizzwhizzer is a website that provides templates for creating interactive games. Even though it is used by beginners, this website is very easy to understand. Training is carried out in the form of One-Day Training (ODT) with structured training. At the end of the activity, the committee asked the training participants to fill out a questionnaire regarding their satisfaction during the training. The results of the questionnaire showed that 89% of participants felt very satisfied and 11% felt satisfied. This shows that this training activity ran smoothly and in accordance with the expectations of the implementing committee.